Surgical treatment of unstable pelvic ring fractures - kezunovic, miroslav b; Bulatović, Nikola (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Pelvic ring fractures are complex injuries and are often associated with internal organs injuries. These injuries require rapid and accurate diagnosis and in some cases one or more surgical interventions. The aim of this retrospective study is to describe the indications and outcomes of surgical treatment of pelvic ring injuries with the emphasis on anatomical reconstruction and stable osteosynthesis as a prerequisite for early mobilization and more favorable functional outcomes. Methods. In the period from 2006 to 2012, fifty-five patients with pelvic ring injuries with or without acetabular fractures were analyzed. The average age of all patients was 36 years. Forty-one patients were treated with operational open reduction and internal fixation (ORIF) while nine of them were treated nonoperatively (bed rest, skeletal traction and external fixation). Results. All operated patients were treated within 3-24 days with ORIF, stable osteosynthesis and early mobilization which resulted in avascular necrosis (AVN) of the femoral head in two cases. AVN of the femoral head was noted in five cases in combined and isolated pelvic ring injuries and acetabulum which were treated with skeletal traction. Neurological deficit was recorded in three patients treated with conservative methods while two patients underwent ORIF. Deep vein thrombosis (DVT) was noted in two patients and pulmonary thromboembolism appeared in one patient 23 days after surgical intervention. Two infections occurred around Steinman pins in the patients who had the definitive treatment performed with external fixator. In one patient treated with ORIF a superficial infection occurred and was treated with antibiotics. The functional results were evaluated based on Merle d’Aubigné score. The results of the radiography treatment were analyzed according to Slatis. Conclusion. Strict application of rational criteria and surgical technique with stable internal fixation with early mobilization provide significantly better outcomes of these injuries in relation to non surgical treatment or treatment with definitive external fixation.